Bibliometric Analysis of Research on Scientific Literacy between 2018 and 2022: Science Education Subject - Mohd Dzul Hakim Wirzal; Nik Abdul Hadi Md Nordin; Mohamad Azmi Bustam; Maria Joselevich (International Journal of Essential Competencies in Education, 2022)
This study presents the results of a bibliometric scientific literacy analysis on science education subjects. The main objectives of this study are (1) to analyze trends in scientific publications on scientific literacy in science education subjects; (2) identification of networks between authors, institutions, and countries; and (3) to understand the structure and focus of research and teaching themes of scientific literacy on science education subject. This research uses 451 published documents from 2018-2022 from the SCOPUS database. VosViewer software is used to analyze and visualize research data. The results of the research show (1) scientific publications on the topic of scientific literacy in science education subject have increased significantly in the last five years; (2) research results on this topic are published in reputable scientific journals (ranked Q1 and Q2); (3) United States is the country with the highest number of documents, citations, and institutions; and (4) there are six groups of keywords used, namely scientific literacy, science education, nature of science, students, education, and teacher education. This study recommends that research at the primary and secondary education levels by taking into account aspects of SL traits can be carried out in future research.